Pengaruh Gaya Hidup Pada Kualitas Hidup Menopause: Systematic Literature Review - Maulidawati; Anita Hellena Wehantouw; Nuriani; Lisa Trina Arlym (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Menopause is a natural phase marked by the cessation of menstruation and a decline in estrogen levels, which impacts physical, psychological, and social health. A healthy lifestyle can help improve quality of life during this period. To analyze the effect of a healthy lifestyle on the quality of life of menopausal women through a review of recent literature. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines, with article searches performed in PubMed, ScienceDirect, SpringerLink, ProQuest, and Google Scholar (2023–2025). Articles were selected based on inclusion and exclusion criteria and analyzed narratively using PICOS tabulation. Of the 107 articles screened, 10 met the inclusion criteria. Interventions included physical activity, a balanced diet, stress management, social support, and health education, all of which consistently improved the quality of life in menopausal women, with significant enhancements in physical, psychological, social, and environmental domains. A healthy lifestyle plays an important role in improving the quality of life during menopause, supporting the development of evidence-based and holistic health promotion programs.